(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sports training is a special process of preparation of sports persons based on scientific principles aimed at improving and maintaining higher performance capacity in different sports activities. It is a particular type of training designed to improve fitness and abilities to perform in a given sport. The purpose of the study is to find out the effect of varied training (Plyometric Training) whether or not any significant difference found between pre-test and post-test on physical fitness among university basket ball players at Hyderabad and their performance.